När faktorer lyser med sin frånvaro: om några typer av betydelsevariation hos svenska idiom - Sköldberg, Emma (HERMES - Journal of Language and Communication in Business, 2005)
In this paper, I explore certain types of semantic variation that recur in 36 Swedish idioms when used in contemporary newspaper material (slightly more than 33.7 million running words). The semantic analysis of the idioms is inﬂ uenced by studies of lexemes. The idioms are described according to the principle of factor analysis, meaning that I have attempted to differentiate semantic factors that can be considered building blocks in the internal semantic structure constituting the conventionalized meaning of the idioms. Deﬁ nitions of the expressions were then based on the semantic factors. One type of variation entails the manifestation of a speciﬁ c semantic factor in certain cases when the idiom is used. Other times, the relevant factor is absent. In a different type of variation, one particular semantic factor is replaced by another. The study reported here should be useful in a variety of ways, including as a basis for comparison between how semantic variation appears in different types of ﬁ xed phrases and lexemes.